2019
DOI: 10.1111/jep.13164
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge gap regarding osteoporosis among medical professionals in Southern India

Abstract: Rationale, aims, and objectives:Osteoporosis is a common health problem in India, which leads to significant morbidity and mortality in elderly individuals. Lack of knowledge and awareness among medical professionals is one of the important barriers in management of these patients. Therefore, this study was conducted to assess knowledge pertaining to diagnosis and treatment of osteoporosis among a group of Indian medical practitioners. Methods:The study participants included 222 allopathic medical professional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…[ 21 ] Few authors from India reported poor awareness of osteoporosis in postmenopausal women are noted. [ 18 22 23 24 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 21 ] Few authors from India reported poor awareness of osteoporosis in postmenopausal women are noted. [ 18 22 23 24 ]…”
Section: Discussionmentioning
confidence: 99%
“…There are more than 100 million postmenopausal women in India, and more than two-thirds of them reside in rural areas. [414] Therefore, primary care physicians and family care practitioners play an important role in pre-emptively screening them for fracture risk. As the availability of DXA scanners is limited in resource poor conditions, FRAX may be utilized to identify those at risk for osteoporotic fractures.…”
Section: Limitations Of the Frax Toolmentioning
confidence: 99%
“…The reasons cited for this include less awareness among primary care and family physicians about the need for referral and treatment, limited access to an ideal diagnostic modality like dual-energy X-ray absorptiometry (DXA) scan, and lack of precise fracture risk prediction tools. [45]…”
Section: Introductionmentioning
confidence: 99%
“…Osteoporosis, which is reported to occur in about 25–60% of Indian postmenopausal women, is a common, yet under recognized public health problem. [ 1 2 ] The lifetime risk of osteoporotic fracture is around 40–50% in women and the mortality rate following fragility fractures is as high as 25% in the first year. [ 3 ]…”
Section: Introductionmentioning
confidence: 99%